Cross-Cultural Understanding in Learning English at IAIN Takengon Students - Vera Ramayana; Hartini Erfi Nurzannah; Muhammad Hasyimsyah Batubara; Mukhlis Lbs (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
Culture is the identity of a country, and as a differentiator between one country and another, the purpose of studying cross-cultural understanding is to understand the differences between cultures in other countries so that there will be no misunderstanding of the culture of one country and another. Therefore, it is essential for students, especially English students. This research is descriptive quantitative research with interviews and observations. The results show that the understanding of the 6th-semester students of the English study program about cross-cultural and language is excellent. In observations and interviews, students understand the cultural rules inherent in other countries, the concept of discipline and respecting time in other countries, and how to respect one's privacy. And students understand the relationship between language and culture.